Pengembangan Bahan Ajar Pada Materi Bangun Datar Kelas 4 Berbasis Pendekatan Open Ended untuk Meningkatkan Penalaran Peserta Didik di Sekolah Dasar Kota Semarang - Norma Tri Yunita; Joko Sulianto; Mira Azizah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this study was to determine the development of teaching materials based on an open ended approach to improve students' reasoning. This study used the Research and Development (R&D) method. The data analysis technique used was descriptive qualitative. The results of the validation of content experts in stage I obtained an average validity of 70.8 with a good category, in stage II, an average validity of 95 was obtained with a very good category. The results of construct validation in stage I obtained an average validity of 71.6 with good criteria, in stage II obtained an average validity of 94.5 with very good criteria. The results of the initial field trial of content validation obtained an average validity of 97.5 with very good criteria and construct validation obtained an average validity of 98.7 with very good criteria. The conclusion is that the Bangun flat teaching material that has been developed is very valid and feasible to use to improve the reasoning abilities of students in grade IV SD N Bendungan Semarang and SD N Kedungmundu Semarang